Pengembangan Media Ajar Berbasis ICT Dalam Pembelajaran Fisika - Nazliah Nazliah; Agus Wahyuni; Samsul Bahri (JURNAL FISIKA EDUKASI, 2014)
The purpose of this research is to develop a Technology For Instructional Media To Improve Teacher Professionalism In Design Media Learning High School Physics / MA in Aceh Province. This study uses a design research and development ( R D ) as a design grant. Respondents in the study were high school physics teacher MA in Aceh Province, set sampling with stratified random sampling technique. Media have been developed subsequently tested through experimentation advisability. To collect the data related to the variables studied, used observation, questionnaires and interviews. Before being used in the study, all first validated instruments. To analyze the data used descriptive analysis techniques. Results showed in general physics teacher in Aceh capabilities are adequate teaching methods and the use of ICT -based media based on the media that researchers offer the suitability of the material 95 % of teachers stated accordingly. Instructional media in general appearance by respondent also good although they need no improvement in sound effects and animated video that runs less well, but for the content of the material, the composition of colors, fonts, explanations of terms and use of language is good. Based on the 2013 mengitegrasi ICT curriculum in learning, especially learning physics, physics To get the quality can be increased, then the teachers need to prepare a field study of physics learning tools, learning materials, exercises and ICT -based media as a guide in the learning process.